Durable response to venetoclax, azacytidine, and ruxolitinib in chronic-phase myelofibrosis resistant to ruxolitinib: a case report and literature review - Liu, Xiaohong; Zhang, Xiujuan; Shi, Hongxia (Frontiers in Oncology, 2025)
Myelofibrosis (MF) is a philadelphia chromosome-negative chronic myeloprolifera- tive neoplasm.It has a worse prognosis than polycythemia vera and essential thrombocy- themia.At present,both Chinese and foreign guidelines recommend ruxolitinib as first-line treatment for IPSS/DIPSS/DIPSS-Plus patients with splenomegaly in intermediate-risk-2 and high-risk MF-CP.However,long-term follow-up revealed possible increase in the discontinuation rate of ruxolitinib due to drug resistance and other reasons with the prolongation of the treatment duration. At this study,it imposes a great challenge for clinical management owing to the lack of standard treatment for patients who have lost efficacy due to drug resistance,and the absence of subsequent treatment strategies. Significantly, venetoclax combined with azacytidine, with or without the use of ruxolitinib, was reported to be effective and safe for patients in MF-accelerated/acute phase.Here, we report a case of MF-CP patient who was unresponsive to ruxolitinib, with therapeutic response after applying venetoclax and azacytidine in combination with ruxolitinib. After treatment, the patient showed improved condition. After two courses of treatment with venetoclax and azacytidine combined with ruxolitinib, the patient has been continuously treated with oral ruxolitinib and has achieved a therapeutic effect for more than 1 year. The treatment response of this patient we reported provides a new safe and effective treatment method for MF-CP patients who are no longer responsive to ruxolitinib.